2012
DOI: 10.1080/14634988.2012.712027
|View full text |Cite
|
Sign up to set email alerts
|

Length weight relationships and fecundity estimates of long-spined Sea Urchin, Diadema setosum, from the Pulau Pangkor, Peninsular Malaysia

Abstract: The present study is an attempt to describe the size frequency distribution, length weight relationships and fecundity estimates of long-spined Sea Urchin, Diadema setosum from the Pulau Pangkor, Peninsular Malaysia. In total 101 specimens of D. setosum were collected from the inter-tidal reef of Pulau Pangkor of Parek during the breeding season in May-August, 2010. Individual total length (TL) was measured using digital slide calipers and individual body weight (BW) was taken using a digital balance. Mean len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
1
9
1
Order By: Relevance
“…Since the Pencil urchin consists of several genera, P. imperialis is considered as one of the new records for Malaysian waters. Compared with previous sea urchin species that had been recorded in coral reefs of Malaysia [10,11,13,14,18], three species are new records (P. imperialis, M. globulus, and P. maculata) and three species were not found in this study (Astropyga radiata, E. diadema, and Parasalenia gratiosa). The total number of sea urchins found in this study was 3,441 individuals.…”
Section: Resultscontrasting
confidence: 62%
“…Since the Pencil urchin consists of several genera, P. imperialis is considered as one of the new records for Malaysian waters. Compared with previous sea urchin species that had been recorded in coral reefs of Malaysia [10,11,13,14,18], three species are new records (P. imperialis, M. globulus, and P. maculata) and three species were not found in this study (Astropyga radiata, E. diadema, and Parasalenia gratiosa). The total number of sea urchins found in this study was 3,441 individuals.…”
Section: Resultscontrasting
confidence: 62%
“…Among the echinoderms, D. setosum is one of the most widely distributed sea urchins, in the Indo-West Pacific Ocean, where it occurs from the Red Sea (Gulf of Suez, Gulf of Aqaba, northern and southern Red Sea) and the east coast of Africa to Japan and Australia (Lessios et al, 2001). The occurrence of D. setosum covers both tropical waters and temperate zones (Rahman et al, 2012). Previous work showed that the gonads of D. setosum also are rich in various bioactive compounds, including polyunsaturated fatty acids (PUFAs) and βcarotene (Dincer and Cakli, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the Caribbean coral reefs, the TD of D. antillarum is 57.0±3.6 mm on the reef slope and 56.9±0.7 mm on the reef edge (Blanco et al 2010). The TD of D. mexicanum in the coral reef of California Bay is 43.8 mm±15.0 (Alvarado et al 2016) and that of D. setosum around Pangkor Island, Malaysia, is 58.73± 5.08 mm (Rahman et al 2012). Therefore, the mean TD of Diadema populations is within a 40-60 mm range.…”
Section: Discussionmentioning
confidence: 89%